2021
DOI: 10.5650/jos.ess20306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Additives on the Interaction of Ciprofloxacin Hydrochloride Drug with Polyvinylpyrrolidone and Bovine Serum Albumin: Spectroscopic and Molecular Docking Study

Abstract: The fluoroquinolone antibiotic drug namely ciprofloxacin hydrochloride (CFH) is widely prescribed for the treatment of different bacterial infections. The interaction of CFH with a synthetic polymer, polyvinyl pyrrolidone (PVP), and biopolymer, bovine serum albumin (BSA) was studied by UVvisible and fluorescence spectroscopic methods at different temperatures. The binding constant (K b ) for the CFH-PVP complex was determined from the Benesi-Hildebrand plot. PVP of different molecular weights (MW) (such as 24,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Furthermore, the salting-out effect of salts as well as the increase of the temperature improved the binding of ciprofloxacin to PVP. 62 Our results agree well with Mukta et al 62 findings. At acidic and basic pH, the D values are more than neutral pH, which is related to the stronger interaction of the ciprofloxacin with PVP that causes a higher concentration of the drug to be transferred to the PVP-rich phase and increases the distribution coefficient (D).…”
Section: ■ Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the salting-out effect of salts as well as the increase of the temperature improved the binding of ciprofloxacin to PVP. 62 Our results agree well with Mukta et al 62 findings. At acidic and basic pH, the D values are more than neutral pH, which is related to the stronger interaction of the ciprofloxacin with PVP that causes a higher concentration of the drug to be transferred to the PVP-rich phase and increases the distribution coefficient (D).…”
Section: ■ Introductionsupporting
confidence: 92%
“…The interaction between ciprofloxacin and PVP was studied by Mukta et al 62 using spectroscopic and molecular docking methods. Molecular docking studies revealed the existence of hydrogen bonding as well as the electrostatic interactions between PVP and ciprofloxacin.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The mixed solution was placed in a water bath to ensure a constant temperature for experiments. [ 26 ] The excitation wavelength was 290 nm, and the emission spectrum range was 280–320 nm. The excitation silt width was set to 2.5 nm and emission silt width was set to 5.0 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The negative value of ΔH o also may mean the existence of weak electrostatic forces between COP and LSL. [26] 3.7 | UV-vis adsorption spectrum…”
Section: Fluorescence Quenching Spectrummentioning
confidence: 99%
“…[13][14][15] In the field of drug delivery systems, the investigation of drugprotein interactions has become prominent, leading to numerous studies. [16][17][18][19][20] Various methodologies have been used to investigate protein-drug interactions, including spectrometry, 21 fluorescence, 22 calorimetry, 23 circular dichroism (CD), 24 molecular modeling, 25 Raman spectroscopy, 26 nuclear magnetic resonance (NMR), 27 and electrochemical methods. [28][29][30][31][32] The voltametric techniques in electrochemical studies are noteworthy techniques due to its speed, efficiency, and cost-effectiveness.…”
mentioning
confidence: 99%